2014 American Control Conference 2014
DOI: 10.1109/acc.2014.6859479
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity measures for spatially decaying systems

Abstract: We consider the omnipresent class of spatially decaying systems, where the sensing and controls is spatially distributed. This class of systems arises in various applications where there is a notion of spatial distance with respect to which couplings between the subsystems can be quantified using a class of coupling weight functions. We exploit spatial decay property of the dynamics of the underlying system in order to introduce system-oriented sparsity measures for spatially distributed systems. We develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…a chain), the QI condition requires that each controller share its measurements with the whole network -this becomes a limiting factor as systems scale to larger and larger size. Although several attempts have been made in the literature to find sparse controllers (which lead to tractable implementations), such as sparsity-promoting control [14], [15], and spatial truncation [16], [17], the synthesis procedure is still centralized. In this paper and our previous work [18], we advocate the importance of locality (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…a chain), the QI condition requires that each controller share its measurements with the whole network -this becomes a limiting factor as systems scale to larger and larger size. Although several attempts have been made in the literature to find sparse controllers (which lead to tractable implementations), such as sparsity-promoting control [14], [15], and spatial truncation [16], [17], the synthesis procedure is still centralized. In this paper and our previous work [18], we advocate the importance of locality (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…So · Cq,w is a quasi-norm [4,14]. Therefore (C q,w , · Cq,w ) forms a quasiBanach algebra by Proposition 2.1.…”
Section: Quasi-banach Algebrasmentioning
confidence: 90%
“…For spatially invariant systems, the optimal controllers with respect to quadratic performance indices (e.g., LQR, H 2 , H ∞ ) are also spatially invariant and they exponentially discount information with spatial distance [2]. Moreover, it has been suggested that optimal controllers for spatially-decaying systems over general graphs also possess spatially-decaying property [84,85]. This motivates the search for inherently localized controllers and suggests that localized information exchange in the distributed controller may provide a viable strategy for controlling large-scale systems.…”
Section: An Examplementioning
confidence: 99%
“…For spatially invariant systems, the quadratic optimal controllers are also spatially invariant and the information from other subsystems is exponentially discounted with the distance between the controller and the subsystems [2]. For systems on graphs, this spatially decaying property was studied in [84,85] and it motivates the search for inherently localized controllers.…”
Section: Introductionmentioning
confidence: 99%